2020
DOI: 10.1590/1516-731320200070
|View full text |Cite
|
Sign up to set email alerts
|

VASI Questionnaire in the context of Brazilian Secondary Education: an Analysis of the Students' Understanding of Scientific Inquiry

Abstract: Science education researchers agree that a better understanding of Scientific Inquiry (SI) is one of the main objectives of Scientific Literacy. Considering the Brazilian scenario in which SI is being implemented as a proposal for science education based on Base Nacional Comum Curricular (BNCC), the aim of this study was to assess the notions of 169 elementary school students regarding SI by administering the VASI questionnaire. This study had a qualitative approach, we categorized the answers in Naïve, Mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Two large-scale international studies with seventh grade (Lederman et al 2019) and high school students (Lederman et al 2021), for example, revealed students from various countries held naïve views about all aspects of SI. Other national studies reached more or less the same conclusion (e.g., Andrade et al, 2020;Gyllenpalm et al, 2022).…”
Section: Discussionsupporting
confidence: 61%
“…Two large-scale international studies with seventh grade (Lederman et al 2019) and high school students (Lederman et al 2021), for example, revealed students from various countries held naïve views about all aspects of SI. Other national studies reached more or less the same conclusion (e.g., Andrade et al, 2020;Gyllenpalm et al, 2022).…”
Section: Discussionsupporting
confidence: 61%